2013
DOI: 10.1186/1810-522x-52-36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of male provisioning on the parental behavior of female Boreal Owls Aegolius funereus

Abstract: Background: Sex-specific parental roles of most raptors allow mates to cooperate during breeding; while females incubate and brood, males provide food. If one partner fails in its parental duties, however, sex-specific parental roles can limit the ability of each sex to carry out the role normally performed by its partner. We observed the effect of male food provisioning on female parental care in Boreal Owls Aegolius funereus using cameras at 12 nests in western Finland in 2005. We compared the parental care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…We also produce a video containing unique information on owl nesting. In the light of previous studies (Zárybnická ; Zárybnická & Vojar ), we confirmed that male Tengmalm's owls deliver most of the prey to the nest, while females incubate the eggs and brood nestlings. Simultaneously, male owls increased their feeding frequency with the nestling age, while the females decreased their time spent in the nest.…”
Section: Discussionsupporting
confidence: 88%
“…We also produce a video containing unique information on owl nesting. In the light of previous studies (Zárybnická ; Zárybnická & Vojar ), we confirmed that male Tengmalm's owls deliver most of the prey to the nest, while females incubate the eggs and brood nestlings. Simultaneously, male owls increased their feeding frequency with the nestling age, while the females decreased their time spent in the nest.…”
Section: Discussionsupporting
confidence: 88%
“…Everyone has an opportunity to analyse basic biological data, e.g., bird activities and behaviour, including food delivery and removal of droppings, in relation to the time of day and the breeding season and also in relation to environmental conditions, such as temperature and light intensity (Fig 3). The data collected by SNBox on Tengmalm’s owl nesting have been of high enough quality to be published in more than ten scientific journals (e.g., [2730]). The BirdsOnline project also has the potential to collaborate with research teams across geographic areas, and it can focus on variable animal taxa.…”
Section: Introductionmentioning
confidence: 99%
“…However, we visited the nestboxes during a period without snow cover and so left no tracks that a potential nest predator could follow. Other failed nesting attempts were caused by nest abandonment during the incubation phase or during the nestling phase with signs of food shortage (no stored prey in the nestbox and disappearance of the youngest nestlings during regular nest visits; Zárybnická & Vojar ).…”
Section: Methodsmentioning
confidence: 99%